Effect of pre-diabetes on future risk of stroke: meta-analysis. (7th June 2012) - Lee, Meng; Saver, Jeffrey L; Hong, Keun-Sik; Song, Sarah; Chang, Kuo-Hsuan; Ovbiagele, Bruce
Abstract : Objectives To assess the association between pre-diabetes and risk of stroke, and to evaluate whether this relation varies by diagnostic criteria for pre-diabetes. Design Systematic review and meta-analysis of prospective studies. Data sources A search of Medline, Embase, and the Cochrane Library (1947 to 16 July 2011) was supplemented by manual searches of bibliographies of key retrieved articles and relevant reviews. Selection criteria Prospective cohort studies that reported multivariate adjusted relative risks and corresponding 95% confidence intervals for stroke with respect to baseline pre-diabetes were included. Data extraction Two independent reviewers extracted data on pre-diabetes status at baseline, risk estimates of stroke, study quality, and methods used to assess pre-diabetes and stroke. Relative risks were pooled using random effects models when appropriate. Associations were tested in subgroups representing different characteristics of participants and studies. Publication bias was evaluated with funnel plots. Results The search yielded 15 prospective cohort studies including 760 925 participants. In 8 studies analysing pre-diabetes defined as fasting glucose 100-125 mg/dL (5.6-6.9 mmol/L), the random effects summary estimate did not show an increased risk of stroke after adjustment for established cardiovascular risk factors (1.08, 95% confidence interval 0.94 to 1.23; P=0.26). In 5 studies analysing pre-diabetes defined as fasting glucose 110-125 mg/dL (6.1-6.9 mmol/L), the random effects summary estimate showed an increased risk of stroke after adjustment for established cardiovascular risk factors (1.21, 1.02 to 1.44; P=0.03). In 8 studies with information about impaired glucose tolerance or combined impaired glucose tolerance and impaired fasting glucose, the random effects summary estimate showed an increased risk of stroke after adjustment for established cardiovascular risk factors (1.26, 1.10 to 1.43; P<0.001). When studies that might have enrolled patients with undiagnosed diabetes were excluded, only impaired glucose tolerance or a combination of impaired fasting glucose and impaired glucose tolerance independently raised the future risk of stroke (1.20, 1.07 to 1.35; P=0.002). Conclusion Pre-diabetes, defined as impaired glucose tolerance or a combination of impaired fasting glucose and impaired glucose tolerance, may be associated with a higher future risk of stroke, but the relative risks are modest and may reflect underlying confounding.